Co-obligate symbioses have repeatedly evolved across aphids, but partner identity and nutritional contributions vary across lineages - Manzano-Marín, Alejandro; Coeur d’acier, Armelle; Clamens, Anne-Laure; Cruaud, Corinne; Barbe, Valérie; Jousselin, Emmanuelle (Peer Community Journal)

(untitled)
Aphids are a large family of phloem-sap feeders. They typically rely on a single bacterial endosymbiont, Buchnera aphidicola, to supply them with essential nutrients lacking in their diet. This association with Buchnera was described in model aphid species from the Aphidinae subfamily and has been assumed to be representative of most aphids. However, in two lineages, Buchnera has lost some essential symbiotic functions and is now complemented by additional symbionts. Though these cases break our view of aphids harbouring a single obligate endosymbiont, we know little about the extent, nature, and evolution of these associations across aphid subfamilies. Here, using metagenomics on 25 aphid species from nine subfamilies, re-assembly and re-annotation of 20 aphid symbionts previously sequenced, and 16S rRNA amplicon sequencing on 223 aphid samples (147 species from 12 subfamilies), we show that dual symbioses have evolved anew at least six times. We also show that these secondary co-obligate symbionts have typically evolved from facultative symbiotic taxa. Genome-based metabolic inference confirms interdependencies between Buchnera and its partners for the production of essential nutrients but shows contributions vary across pairs of co-obligate associates. Fluorescent in situ hybridisation microscopy shows a common bacteriocyte localisation of two newly acquired symbionts. Lastly, patterns of Buchnera genome evolution reveal that small losses affecting a few key genes can be the onset of these dual systems, while large gene losses can occur without any co-obligate symbiont acquisition. Hence, the Buchnera-aphid association, often thought of as exclusive, seems more flexible, with a few metabolic losses having recurrently promoted the establishment of a new co-obligate symbiotic partner.